2017
DOI: 10.1002/2017jb013930
|View full text |Cite
|
Sign up to set email alerts
|

Geographic variations in lowermost mantle structure from the ray parameters and decay constants of core‐diffracted waves

Abstract: We introduce an array‐based approach for constraining seismic velocity structure in the lowermost mantle by measuring the frequency dependence of the ray parameter p and decay constant γ for core‐diffracted waves (Pdiff and SHdiff). The approach uses an iterative multichannel cross‐correlation algorithm that solves for relative arrival times and amplitudes of core‐diffracted waveforms from multiple peaks in normalized correlograms from pairs of coazimuthal stations. The approach is applied to 60 mb ≥ 5.8 earth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 137 publications
1
8
0
Order By: Relevance
“…Moreover, in the same region the authors recorded a decrease in the amplitude decay constant, that is, less decay with distance, consistent with our waveform simulation showing greater amplitudes as a function of distance relative to the reference. While the study of Euler and Wysession (2017) lacks the spatial coverage and frequency range to be directly compared against our predictions, the observations of the patterns of core diffracted waves are encouragingly similar to the manifestation predicted for our TBL model.…”
Section: Seismic Confirmation Of a Thermal Boundary Layersupporting
confidence: 71%
See 1 more Smart Citation
“…Moreover, in the same region the authors recorded a decrease in the amplitude decay constant, that is, less decay with distance, consistent with our waveform simulation showing greater amplitudes as a function of distance relative to the reference. While the study of Euler and Wysession (2017) lacks the spatial coverage and frequency range to be directly compared against our predictions, the observations of the patterns of core diffracted waves are encouragingly similar to the manifestation predicted for our TBL model.…”
Section: Seismic Confirmation Of a Thermal Boundary Layersupporting
confidence: 71%
“…The most comprehensive study of Pdiff waveform variations are from Euler and Wysession (2017), who measured regional variation in slowness anomalies and amplitude decay constant for Pdiff as a function of wave frequency, which is inversely proportional to the thickness of the layer that waves are sensitive to at the CMB. Some regions that are distant from the LLSVPs, such as under northern Asia, displayed increasing slowness with increasing sensitivity close to the CMB on the order of 0.1 s/°, consistent with predictions from our TBL model.…”
Section: Discussionmentioning
confidence: 99%
“…Recent large scale deterministic P-wave tomographic results with significant sensitivity to the lowermost mantle obtained by Pdiff data sets, reported by Hosseini et al (2020), have also indicated substantial structural complexity with the most predominant features being a fast patch under East Asia and a wide, quasihemispherical slow band that includes the locations of the African and Pacific LVPs. Pdiff data sets provide the most comprehensive coverage of lowermost mantle Vp structure (Hosseini & Sigloch 2015;Euler & Wysession 2017), however their maximum frequency content is limited by the diffraction process and so our high-frequency PcP-P and PKPab-PKPbc provide useful additional constraints on the finer scale structure of the lowermost mantle region. Quantifying these observations, Fig.…”
Section: Discussion a N D C O N C L U S I O N Smentioning
confidence: 99%
“…Resulting chemical heterogeneity together with laterally varying temperature profiles and phase transitions cause significant spatial variability in the elastic properties of the lower mantle. Images of D″ have been provided by global seismic tomography studies (Kustowski et al., 2008; Ritsema et al., 2011) while its internal structure is constrained generally using top and bottom reflections as well as transmitted and diffracted wave observations (Euler & Wysession, 2017; Frost & Rost, 2014; Hansen et al., 2020; Shen et al., 2016; Sun et al., 2013; Wang & Wen, 2004). A review of seismic investigations of the lower mantle can be found in Lay and Garnero (2011).…”
Section: Wave Scattering In the Deep Earthmentioning
confidence: 99%